Adsorption of fluoride from aqueous solution by Bio-F sorbent: a fixed-bed column study. Issue 14 (21st March 2016) - Yadav, Manish; Tripathi, Priya; Choudhary, Aditya; Brighu, Urmila; Mathur, Sanjay
Abstract: In this work, the adsorption potential of Bio-F to remove fluoride from aqueous solution was investigated using fixed-bed adsorption column. The effects of inlet fluoride concentration (10–30 mg/L), feed flow rate (10–30 mL/min), and Bio-F bed height (10–20 cm) on the breakthrough characteristics of the adsorption system were determined. The highest bed capacity of 9.867 mg/g was obtained using 30 mg/L inlet fluoride concentration, 10 cm bed height, and 20 mL/min flow rate. The adsorption data were fitted to three well-established fixed-bed adsorption models namely, Adam's–Bohart, Thomas, and Yoon–Nelson models. The results fitted well to the Adam's–Bohart and Yoon–Nelson models with low sum of square errors at different conditions. The Bio-F was found to be a suitable adsorbent for adsorption of fluoride using fixed-bed adsorption column.